2007
DOI: 10.1111/j.1365-2656.2007.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Army ants in four forests: geographic variation in raid rates and species composition

Abstract: Summary1. The New World army ants are top predators in the litter of tropical forest, but no comprehensive studies exist on variation in assemblage-wide activity and species composition. We used standardized protocols to estimate foraging raid rates and species composition of army ant communities in four Neotropical forests. The study sites spanned approximately 10 ° latitude, with two sites each in Central and South America. 2.We recorded a total of 22 species of army ants. The four sites varied in observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 45 publications
1
93
0
1
Order By: Relevance
“…The dearth of army ants in our samples reflects the fact that this group is primarily found in structurally more heterogeneous physiognomies, such as forests, and are usually less diverse and harder to observe in open fields and savannas (Baccaro et al, 2015). However, this result can also be due to short sampling period (see O'Donnell et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…The dearth of army ants in our samples reflects the fact that this group is primarily found in structurally more heterogeneous physiognomies, such as forests, and are usually less diverse and harder to observe in open fields and savannas (Baccaro et al, 2015). However, this result can also be due to short sampling period (see O'Donnell et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…The activity of E. burchellii swarms declines in the afternoon at La Selva (O'Donnell et al 2007), so we collected nearly all samples before noon and recorded the hour in which each observation was made. The size (width) of the swarm can affect prey intake through competition (Willson 2004) and was visually estimated from the blind (to prevent disturbance) to the closest metre at the end of each observation period.…”
Section: Methodsmentioning
confidence: 99%
“…Weather conditions affect E. burchellii activity (O'Donnell et al 2007) and were measured during each sampling period by an automatic meteorological station (ambient temperature, precipitation and humidity). The activity of E. burchellii swarms declines in the afternoon at La Selva (O'Donnell et al 2007), so we collected nearly all samples before noon and recorded the hour in which each observation was made.…”
Section: Methodsmentioning
confidence: 99%
“…We know very little on the biology of Cheliomyrmex species; O'Donnell et al (2005) reported that C. andicola prey on large-bodied ground dwelling invertebrates and, probably, vertebrates, using (possibly) their unusual mandibles and stings to pierce and grip the integument of non-arthropod prey animals, and for rapidly subduing large-bodied prey, respectively. Despite the abundance of Ecitoninae in Neotropical forests (Kaspari & O'Donnell, 2003), data on the structure of their communities and ecological impacts are limited (O'Donnell et al, 2007, but see Berghoff et al, 2008, and included references for Panama's Canal Zone). Most of what is known about the biology of Ecitoninae is derived from observations on the behavior of Eciton burchelli (see Gotwald, 1995;O'Donnell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the abundance of Ecitoninae in Neotropical forests (Kaspari & O'Donnell, 2003), data on the structure of their communities and ecological impacts are limited (O'Donnell et al, 2007, but see Berghoff et al, 2008, and included references for Panama's Canal Zone). Most of what is known about the biology of Ecitoninae is derived from observations on the behavior of Eciton burchelli (see Gotwald, 1995;O'Donnell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%